Autocrine Control of Angiogenesis by Endogenous Acetylcholine in an In Vitro Model Using Human Endothelial Cells: Evidence for an Autocrine Cholinergic System in Endothelial Cells. Issue 5 (May 2015) - Dhein, Stefan; Wermke, Alice; von Salisch, Sandy; Schlegel, Franziska; Stepan, Holger; Dohmen, Pascal Maria; Kostelka, Martin; Mohr, Friedrich-Wilhelm
Abstract : Abstract: We wanted to elucidate whether acetylcholine as the endogenous ligand at cholinoceptors (ChRs) may have effects on angiogenesis and whether they are transduced through muscarinic or nicotinic ChRs. Human umbilical vein endothelial cells were cultured until confluence and thereafter seeded in Matrigel in vitro angiogenesis assays for 18 hours. During the entire cell culture and angiogenesis period, cells were treated with vehicle, eserine (1 μM), in the absence or presence of additional atropine (1 μM) or mecamylamine (1 μM). Finally, the resulting angiogenetic network was investigated histologically. Eserine significantly enhanced acetylcholine formation. When acetylcholine acted through muscarinic ChRs (eserine + mecamylamine), we observed enhanced complexity of the angiogenic network pattern with increased tube length and cell number. In contrast, when acting through nicotinic ChRs (eserine + atropine), we found reduced complexity of pattern with less branches, shorter tubes, and reduced cell number. If acting on both types of ChRs (eserine alone), there were only very small effects. Using α-bungarotoxin, lobeline, and dihydro-β-erythroidine, we also could show that these effects to various degrees involve α7, α3/β2, and α4/β2 n-ChRs. In conclusion, our results support the hypothesis that human umbilical vein endothelial cells possess an autocrine nonneuronal cholinergic system regulating angiogenesic branch formation through the partially opposing effects of n-ChRs and m-ChRs.